A study on echocardiographic findings in hospitalized patients with connective tissue diseases. (4th March 2022) - Weiß, K; Schmidt, WA; Krause, A; Schäfer, VS
Abstract : Objective: To determine the prevalence of echocardiographic findings and their change over time in patients with connective tissue diseases (CTDs) and to analyse which findings were associated with escalation of immunosuppressive therapy. Method: We conducted a retrospective cohort study of consecutive hospitalized patients from a tertiary rheumatology referral centre who received transthoracic echocardiography between 1 January 2006 and 31 December 2015. We tested for associations between echocardiographic findings and treatment escalation via Fisher's exact test; p < 0.05 was considered significant. Escalation of therapy was defined by dosage of glucocorticoids and type of disease-modifying anti-rheumatic drug. The clinical relevance of echocardiographic findings concerning change in immunosuppressive therapy was recorded. Results: In total, 1004 patients were included (865 females), with a total of 1660 echocardiographic examinations. The most frequent findings were mitral, tricuspid, and aortic valve regurgitation (found in 36.7%, 25.4%, and 17.7% of all patients), aortic valve sclerosis (20.1%), left ventricular dysfunction (21.5%), and left atrial dilatation (19.2%). Only pericardial effusions were more frequent in cases with treatment escalation (10.9% of cases with escalated therapy vs 6.9% of cases without, p = 0.007). In 314 patients who received follow-up examinations, echocardiographic findings were found to change between examinations. Only 73 of all 1660 examinations were discussed in depth considering the treatment strategy in the hospital discharge letter. Conclusion: Patients with CTDs exhibited a wide, dynamically changing spectrum of echocardiographic abnormalities. Most findings neither reflected disease activity nor appeared to influence the therapeutic regimen.